Caso de estudio: exportación de baldosas de porcelanato para el mercado estadounidense - Mamani Caro, Melissa Alejandra (2019)
This paper presents the proposal of export of porcelain tiles to the US market, specifically to distributors who import both red and white body tiles in their various sizes. The first chapter describes the profile of the country of destination, relevant socio-economic political characteristics and analysis of the consumer of tiles. Also, the demand for the product explaining the level of import and national production they have in ceramic and porcelain tiles. As well as, the manufacturer's capacity and its quality parameters that can meet all market requirements are detailed such us ANSI and ASTM parameters. In the second chapter, the marketing strategy is presented to achieve the proposed objectives, both enhancing the quality of the product, the competitive price, the distribution channel to develop and the promotional strategy that is mostly linked to the work of the US importer. Therefore, it is concluded that the United States is an attractive market for the proposed plan and it is confirmed that the product would be competitive at the market.